2017
DOI: 10.1093/erae/jbx002
|View full text |Cite
|
Sign up to set email alerts
|

Consumer preferences for fair labour certification

Abstract: High profile cases of exploitative labour practices have increased concerns over agricultural working conditions. However, it is unclear to what extent the public is willing to trade-off fair working conditions for higher prices. We implement a large-scale survey to uncover consumer preferences for a food labeling system that certifies fair working conditions for the workers employed in agricultural production. We test for several methodological issues * We'd like to thank the Editor and two anonymous reviewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 58 publications
(82 reference statements)
2
17
1
Order By: Relevance
“…By carrying out a systematic literature review, Cerri et al (2019) find that the vast majority of studies on sustainable food consumption and preferences neither discuss the thread that SDB stipulates to the validity of results nor offer any kind of remedy for it. While contingent valuation methods, such as the one applied here, are commonly used in surveys, their use is still somewhat controversial regarding the influence of hypothetical bias (Drichoutis et al, 2017). As Blumenschein et al (2008: 114) indicate: "A the heart of this controversy is the extent to which hypothetical choices correspond to real economic choices," and as indicated above, ways to capture consumers "hypothetical" WTPs typically result in greater WTP than "real" WTP measurement instruments (e.g.…”
Section: Starting Point For Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…By carrying out a systematic literature review, Cerri et al (2019) find that the vast majority of studies on sustainable food consumption and preferences neither discuss the thread that SDB stipulates to the validity of results nor offer any kind of remedy for it. While contingent valuation methods, such as the one applied here, are commonly used in surveys, their use is still somewhat controversial regarding the influence of hypothetical bias (Drichoutis et al, 2017). As Blumenschein et al (2008: 114) indicate: "A the heart of this controversy is the extent to which hypothetical choices correspond to real economic choices," and as indicated above, ways to capture consumers "hypothetical" WTPs typically result in greater WTP than "real" WTP measurement instruments (e.g.…”
Section: Starting Point For Experimentsmentioning
confidence: 99%
“…The literature offers several solutions for hypothetical bias. For example, ex-ante methods, such as cheap talk or consequentiality scripts, have been proposed and applied (e.g., Drichoutis et al, 2017;Britwum and Yiannaka, 2019). However, their effect regarding the removal of the hypothetical bias is still somewhat ambiguous (Andor et al, 2014).…”
Section: Expressed Certaintymentioning
confidence: 99%
“…Some extrinsic attributes only provide external benefits and do not necessarily affect the intrinsic attributes of food. Consumers show a preference and willingness to pay for these attributes such as animal welfare [14][15][16] and fair trade or labor practices [17][18][19] for the benefit to the public instead of their own individual benefit.…”
Section: Background and Literaturementioning
confidence: 99%
“…Regarding the methodologies, the literature review revealed that WTP for low CF products was primarily estimated by hypothetical choice experiments. In only seven studies non-hypothetical methods were used, namely, experimental auctions in four cases (e.g., Chen, Zhang, Huang, & Zheng, 2017) and a real choice experiment in three cases (e.g., Drichoutis, Lusk, & Pappa, 2016;Drichoutis, Vassilopoulos, Lusk, & Nayga, 2017).…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
“…Those changes let emerge the behavior of the respondent that gives extreme importance to the specific characteristic, or belong to higher income The WTP individual amount has been modeled as dependent on the explanatory independent variables listed in Table 1 and an interval regression model has been estimated to investigate the determinants of consumers' WTP for products with lower CF. The interval regression model was chosen because, like in other studies on this topic (Drichoutis et al, 2016(Drichoutis et al, , 2017, the estimates are easier to interpret and the variance of WTP is directly estimated (Hanemann & Kanninen, 2001). Table 2 summarizes the model estimates.…”
Section: A Pilot Online Survey In Italymentioning
confidence: 99%